Graft versus-host disease following allogenic bone marrow transplantation (مجلة البحوث الأكاديمية, 2021)
Aplastic anaemia is a severe haematological disorder characterized by an inadequate number of hematopoietic stem cells, resulting in pancytopenia, formed by a hypocellular bone marrow. Disorders of this nature are widely treated with haematopoietic stem cell transplantation (HSCT). A potential chronic complication following (HSCT) is the growth of secondary malignancies. Notably, patients suffering from chronic graft versus host disease (cGvHD) secondary to HSCT have been shown to be more susceptible to oral squamous cell carcinoma (OSCC). Here, we present a rare case of a 30 year old Libyan woman treated with HSCT for aplastic anaemia, with subsequent complications of cGvHD and OSCC after few months of HSCT. These carcinomatous lesions were detected in the buccal gingiva and retromolar pad area at age of 31 year-old Libyan woman. The present case report emphasizes on the connection between oral cGvHD and OSCC, and the potential appearance of OSCC after HSCT at any time of patient life. Thus, closer follow-up is mandatory for all patients treated with HSCT who developed cGvHD, and efficient cGvHD prevention and therapeutic approaches are needed.